Influence of alveolar bone level on the pull-out bond strength of fiber-reinforced composite posts to root dentin - De Oliveira Dal Piva, Amanda Maria [UNESP]; Campos, Fernanda [UNESP]; Alves, Maria Luiza Lima; Sousa, Rafael Santiago; Da Costa Lima, Julia Magalhães; Souza, Rodrigo Othávio Assunção (My University, 2016)
This in vitro study evaluated the influence of alveolar bone level and type of cement on pull-out bond strength between different fiberreinforced composite (FRC) posts and root dentin. Sixty bovine teeth were sectioned, and their root canals were prepared. The specimens were divided into 6 groups (n = 10) according to 2 factors: Alveolar bone level and type of cement. Each root was embedded in acrylic resin to the depth of 7, 10, or 14 mm, simulating different alveolar bone levels. After the FRC posts were treated with 37% phosphoric acid and silane was applied, they were cemented with either a conventional resin cement or a self-Adhesive resin cement and subjected to mechanical cycling. The results indicated that neither the alveolar bone level nor the type of cement played a significant role in the pull-out bond strength of the FRC posts to root dentin. Therefore, it is concluded that conventional and self-Adhesive resin cements can be used to lute FRC posts to tooth roots, even in the presence of significant alveolar bone resorption.
Keywords: Alveolar bone loss; Fiber-reinforced composite post; Resin cements; Tensile strength